Development of a Recombinant Retrovirus Expressing the Chicken Anaemia Virus Vp3 Protein - Mohd Saad, Suria (2006)

(untitled)
Retrovirus is an infectious particle, hence it could be used as an efficient vector to deliver a desired gene product into mammalian cells. In this study, a recombinant viral vector was employed to carry a gene that induces apoptosis in various transformed and cancerous cell lines. The VP3 gene was cloned into pMSCV plasmid and the recombinant was used to transfect a packaging cell line to produce infectious replication-incompetent recombinant VP3-retrovirus. The sequence of the full length ORF encoding VP3 gene is similar to that of the reference CAV Cux-1 strain indicating that the VP3 gene was stably integrated into the RNA genome of the recombinant retrovirus. Real-time RT-PCR analysis showed virus production in packaging cells increased from day one, but gradually decreased on day three and day four and eventually were undetectable on day five post-infection. The number of packaging cells undergoing apoptosis was shown to be directly associated with recombinant VP3-retrovirus replication and the rate of cell-to-cell infection. Cells infected by recombinant VP3-retrovirus expressed the VP3 protein in transformed and cancerous cell lines as confirmed by indirect immunoperoxidase assay using anti-VP3 monoclonal antibody. The VP3 protein was detected primarily in the nucleus of infected cells, the site in which the protein is believed to initiate the cascade of programmed cell death or apoptosis. Apoptotic genomic DNA cleavage of the transformed cells was observed. Terminal deoxynucleotidyl transferase-mediated dUTP nick end labelling (TUNEL) assay confirmed the occurrence of apoptosis following infection by the recombinant VP3-retrovirus. This study demonstrated the potential application of recombinant VP3-retrovirus in cancer therapy. The current recombinant VP3-retrovirus construct may serve as an excellent prototype for the generation of alternative therapy to prevent the progressive growth of many types of cancer cells